Maternal and Fetal Blood Pharmacokinetics and Organ Distribution of Atrazine, Propazine, Simazine, and Their Metabolites in Pregnant Rats After Chronic Oral Administration. (6th November 2019) - Brandhonneur, Nolwenn; Hutin, Vincent; Chevrier, Cécile; Cordier, Sylvaine; Le Corre, Pascal
Abstract: Environmental contamination by chlorotriazines has been evidenced in mother-child cohort suggesting more detailed risk assessment of these compounds in drinking water. Exposure of rodents to atrazine (ATZ) has been associated with alterations of endocrine and reproductive functions by disrupting neuroendocrine control at hypothalamus level. Perinatal exposure to low doses of ATZ has been associated with reproductive dysfunction, and to behavioral abnormalities in adult exposed during embryogenesis. The objectives of the current investigation were to (1) evaluate the influence of physicochemical properties of chlorotriazines on tissue distribution in pregnant rats and in fetuses and (2) gain a better understanding of fetal distribution of chlorotriazines in specific tissues, particularly in brain. Serial blood samples were obtained from pregnant rats after administration of ATZ, propazine (PRO), and simazine (SIM) via oral route at a dose of 10 mg/kg from day 15 to day 19. Maternal and fetal tissues were harvested at day 20, 24 h after the last dosing. The metabolic extraction ratio was estimated to 87% suggesting a significant first-pass effect explaining the low oral bioavailability. Blood exposure to parent compounds (ATZ, PRO, and SIM) was negligible (lower than 5%) compared with metabolite exposure. The main metabolite exposure involved diamino-s-chlorotriazine, ranging from 60% to 90% depending on the molecules administered. A correlation between tissue-to-blood ratio and physicochemical descriptors was observed for fat and mammary gland tissues but not for brain in adult rats. A more pronounced distribution in fetal brain was observed for ATZ and PRO, the 2 most lipophilic compounds.